Pengaruh Kegiatan Remaja Masjid Al-Istiqlal terhadap Perilaku Keagamaan Remaja di Desa Siku Kecamatan Empat Petulai Dangku Kabupaten Muara Enim - Elles Gasela; Candra Darmawan (Social Science and Contemporary Issues Journal, 2023)
This study entitled "The Influence of Youth Activities at the Al-Istiqlal Mosque on the Religious Behavior of Youth in Siku Village, Empat Petulai Dangku District, Muara Enim Regency". The purpose of this study was to determine the effect of youth activities at the Al-Istiqlal mosque on the religious behavior of adolescents in Siku Village, Empat Petulai Dangku District, Muara Enim Regency. This research uses quantitative methods. Data collection techniques used in this study using observation, interviews, questionnaires and documentation. Sampling was carried out using a total sampling technique, namely the technique of taking all samples from the population, where the population totaled 40 people. The data analysis technique used is simple linear regression analysis by testing the hypothesis t test (partial test) and testing the coefficient of determination (R Square). Data processing was assisted by the SPSS Version 23 program. The results of this study indicated that there was an influence of youth mosque activities on adolescent religious behavior. This is evidenced by the t (partial) test obtained by tcount of 9.421 > ttable of 2.024, and the magnitude of the coefficient of determination (R Square) of 0.700 is equivalent to 70%, which means that the influence of the variable Mosque Youth Activities (X) on the Religious Behavior of Youth (Y), while the remaining 30% is influenced by other factors not examined. Keywords: Influence, Youth Mosque Activities, and Religious Behavior of Youth